Oxygen Monitor to Study Vascularization of Medical Devices. (2020) - Najdahmadi, Avid; Gurlin, Rachel; Zhang, Mellonie; Lakey, Jonathan RT; Botvinick, Elliot
Abstract: Prevascularized medical devices can improve cell therapy. Such devices may replace whole organ transplantation with hosting only the necessary therapeutic cells. We have developed a noninvasive optical technology to study the vascularization into such medical devices. In our technique, oxygen partial pressure within a device is monitored by Oxygen Sensitive Tubes (OSTs), comprising oxygen permeable silicone tubing with inner luminal surfaces coated by an oxygen-sensitive porphyrin dye. OSTs were placed within a PDMS device and transplanted into the subcutaneous space of athymic nude mice. An optical probe placed over the skin excites the OSTs with a pulse of light and detects the luminescent lifetime of emitted light, which is uniquely related to oxygen partial pressure. Furthermore, we developed a Dynamic Inhalation Gas Test (DIGT) to determine the oxygen transport rate between the microvasculature and the device. DIGT works by monitoring oxygen partial pressure in a device following a step change in inhaled-gas oxygen content. We report DIGT oxygen dynamics measured intermittently over eight weeks. Our study shows DIGT dynamics are unique to each implant, supporting the important role of the host tissue response in the availability of oxygen over time.